The art and science of the church screen in medieval Europe : making, meaning, preserving - Bucklow, Spike; Marks, Richard Bruce; Wrapson, Lucy (Boydell studies in medieval art and architecture., 2017)
The churches of medieval Europe contained richly carved and painted screens, placed between the altar and the congregation; they survive in particularly high numbers in England, despite being partly dismantled during the Reformation. While these screens divided "lay" from "priestly" jurisdiction, it has also been argued that they served to unify architectural space. This volume brings together the latest scholarship on the subject, exploring in detail numerous spects of the construction and painting of screens, with contributions from conservators, religious historians, art historians and conservation scientists.